Assessing the Sensitivity of Plasmopara halstedii Isolates to Mefenoxam through Host Responses - Nisha Nisha; Sergey Vinogradov; Katalin Körösi; Arbnora Berisha; Rita Bán (Microorganisms, 2023)
Downy mildew caused by Plasmopara halstedii is responsible for significant economic losses in cultivated sunflowers. Field isolates of sunflower downy mildew resistant to mefenoxam, a previously effective active ingredient against the pathogen, have been found across Europe. The main goal of this study was to assess the sensitivity of P. halstedii isolates to mefenoxam through host responses to infection, such as symptoms measured by disease severity and growth reduction, and host tissue reactions, such as hypersensitive reaction and necrosis of invaded cells. Sunflower seeds were treated with Apron XL 350 FS at the European registered rate (3 mg/kg seeds). Seedlings were inoculated using the soil drench method with eight Hungarian P. halstedii isolates. Disease rates and plant heights were measured twice. Histological examinations of cross-sections of sunflower hypocotyls were performed using a fluorescence microscope. In our study, cluster analyses of sunflowers based on macroscopic and microscopic variables showed differentiation of groups of mefenoxam-treated sunflowers inoculated with different P. halstedii isolates. We first revealed a clear difference in host responses of mefenoxam-treated susceptible sunflowers. In addition, examining tissue reactions (e.g., hypersensitive reaction, necrosis) seems more accurate to estimate the sensitivity of P. halstedii isolates to mefenoxam than macroscopic symptoms.